2017
DOI: 10.1186/s13054-017-1811-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfibrinolysis in severe isolated traumatic brain injury may occur without tissue hypoperfusion: a retrospective observational multicentre study

Abstract: BackgroundHyperfibrinolysis is a critical complication in severe trauma. Hyperfibrinolysis is traditionally diagnosed via elevated D-dimer or fibrin/fibrinogen degradation product levels, and recently, using thromboelastometry. Although hyperfibrinolysis is observed in patients with severe isolated traumatic brain injury (TBI) on arrival at the emergency department (ED), it is unclear which factors induce hyperfibrinolysis. The present study aimed to investigate the factors associated with hyperfibrinolysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…There are three major hypotheses for the mechanism of coagulopathy after trauma: that massive transfusion and infusion in initial treatment after trauma dilute the blood, resulting in a shortage of blood coagulation factors; 11,12) that hypotension induces protein C activation, which activates fibrinolysis; 13) and that tissue factors are released from TBI-damaged brain tissues into the blood, and the coagulation cascade is then activated by these factors. 14) We have shown a relationship of brain injury with D-dimer levels in mild isolated TBI in previous studies, 7,8) and patients without blood dilution due to massive transfusion and infusion or hypotension during treatment still have abnormalities in the coagulation and fibrinolytic system 21) that are not associated with the mechanism of coagulation disorder after TBI. The results of this study suggest that sTF is involved in the mechanism of coagulopathy after TBI.…”
Section: Discussionmentioning
confidence: 85%
“…There are three major hypotheses for the mechanism of coagulopathy after trauma: that massive transfusion and infusion in initial treatment after trauma dilute the blood, resulting in a shortage of blood coagulation factors; 11,12) that hypotension induces protein C activation, which activates fibrinolysis; 13) and that tissue factors are released from TBI-damaged brain tissues into the blood, and the coagulation cascade is then activated by these factors. 14) We have shown a relationship of brain injury with D-dimer levels in mild isolated TBI in previous studies, 7,8) and patients without blood dilution due to massive transfusion and infusion or hypotension during treatment still have abnormalities in the coagulation and fibrinolytic system 21) that are not associated with the mechanism of coagulation disorder after TBI. The results of this study suggest that sTF is involved in the mechanism of coagulopathy after TBI.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, on sub-group analysis of patients with severe brain injury, although there were no significant differences, we observed that early FC administration tended to improve the survival rate of the patients. In patients with severe brain injury, hyperfibrinolysis is frequently observed at admission to the ED [43,44]; this contributes to enlargement of intracranial haematomas, trauma-induced coagulopathy, and poor outcomes [43,[45][46][47]. In this context, FC may help restore haemostasis by complementing plasma fibrinogen, which deteriorates owing to hyperfibrinolysis in patients with severe brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…TRALI is defined according to the Toronto definition, 17 and sepsis is defined according to sepsis-3. 18 Sample size In our previous retrospective multicentre observational study, wherein data were collected from 796 patients with severe trauma from 15 hospitals during a 1-year period, [19][20][21][22][23][24][25][26] 241 patients received RBC concentrates during the first 24 hours after arrival at the ED and 25% of the patients transfused with RBC concentrates died within 28 days after arrival at the ED. Based on these results, we assumed a mortality rate of 25% at 28 days after arrival in the ED among patients receiving a liberal RBC transfusion strategy.…”
Section: Secondary Outcomesmentioning
confidence: 99%